ULTRASONIC DEGRADATION OF ORGANIC POLLUTANTS - Arroyo C., Juan (2001)
Ultrasound has demostrated to be a great source of energy and it has shown its utility In organic synthesis and other technological areas. At the present, most of the research in this areas are driving towards the study of degradatlon of chemical pollutants from wastewater or efluents. In this artlcle we describe the fundamental aspects of sonochemistry and its difierent applicatlons, putting special emphasis on those related to the degradatlon of most important organic pollutants.